Fenomena Calon Tunggal Dalam Pemilihan Umum Kepala Daerah Kabupaten Pati 2017 (Studi Kasus: Sistem Rekrutmen Calon Oleh Partai Politik) - Safira Yuristianti; Fitriyah . (Journal of Politic and Government Studies, 2018)
This research explains the system of candidate recruitment performed by political party in General Election of Pati District Head 2017 based on three empirical observations. First, based on the number of votes of Pati Regional House of People’s Representative (DPRD) in which from year to year each party always carries its candidates to follow the Legislative Election. The second observation in the General Election of District Head 2016 and 2011 in Pati Regency, it was still used the same pattern, namely the political parties from various streams and each political party carried its own candidates to compete. The third observation in General Election of Pati District Head 2017 generated a unique polemic, that there was only one candidate pair that was incumbent. This study examines the problems dealing with, first, how is the political dynamics of Pati District? Second, how is the system of candidate recruitment by political party so that it can bring up a single candidate in General Election of Pati District Head 2017? Third, how is the pragmatic side of the emergence of a single candidate in the General Election of Pati District Head 2017. The research method used was qualitative case study. The result of the research concludes that the political party in determining the candidate depends on survey result and the process of recruitment of candidate by political party is pragmatic.  Keywords: Single Candidate; General Election of District Head; Recruitment System, Pragmatism